Morphological descriptions of the female, pupa, and larva of Culex (Culex) cuyanus Duret (Diptera: Culicidae) - Rossi, Gustavo C.; Scheibler, Erika; Dominguez, Martha C. (Zootaxa, 2006)
The female, pupa, and larva of Culex (Culex) cuyanus are described for the first time, diagnostic characters are given, and the larva and pupa are illustrated. The species is present in La Rioja, San Juan, and Mendoza Provinces in Argentina, where it breeds in semi-permanent pools.